Effects of Red Mold Rice Produced from Monascus purpureus CMU002U on Growth Performances and Antioxidant Activity of Japanese Quail - Kongbuntad, W.; Saenphet , S. (International Journal of Poultry Science, 2015)
This study researched the effects of red rice produced from San-Pah-Tong sticky rice (Oryzae sativa L.cv. Niew San-pah-tawng) and Monascus purpureus (Specie CMU002U). The study was divided into two parts. The first part consisted of a phytochemistry test and tests to determine ascorbic acid and phenolics. Terpenoids, triterpenoids, flavonoids, phenols, phlobatannins and coumarins were found. Phenolic and ascorbic acid levels were 3.00 μg ascorbic acid equivalent/g extract and 1.89 mg Gallic acid equivalent/g extract, respectively. The second part was an experiment using 75 Japanese quails in egg stage randomly divided into four groups as follows: the control group and groups in which each quail was fed with 6, 12 and 24 mg. red rice powder in capsules per day, respectively for 8 weeks. The Manlondialdehyde (MDA) from the serum and liver was then checked. It was found that the serum of the group which received 24 mg a day had reduced levels of MDA in the serum and liver. Compared with the control group, the difference was statistically significant at (p